1974
DOI: 10.1128/am.27.2.400-406.1974
|View full text |Cite
|
Sign up to set email alerts
|

Pyocin Typing of Pseudomonas aeruginosa : a Simplified Method

Abstract: A simplified method has been devised for typing Pseudomonas aeruginosa by pyocin production. Pyocins are produced as strains grow overnight in Trypticase soy broth (without glucose) plus 1% potassium nitrate. Because P. aeruginosa can use nitrate instead of oxygen as a terminal electron acceptor, mechanical shaking is not necessary, nor is induction by mitomycin C. Pyocins can now be produced in screw-cap tubes in a water bath or incubator. A total of 250 strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Importantly, during this period, it was found that R-type pyocins have a more efficient killing activity than headless mutants of a related phage, supporting the hypothesis that these particles are not simply defective prophages but evolved weapons ( Shinomiya and Shiga, 1979 ). Additionally, their advantage for medical use was explored, employing pyocins for P. aeruginosa typing ( Farmer and Herman, 1969 ; Rose et al, 1971 ; Edmonds et al, 1972 ; Lovrekovich et al, 1972 ; Jones et al, 1974 ; Duncan and Booth, 1975 ; Bruun et al, 1976 ; Fyfe et al, 1984 ; Schable et al, 1986 ) as well as a potential treatment against P. aeruginosa infections ( Merrikin and Terry, 1972 ; Haas et al, 1974 ). In addition to all these findings, a new type of phage tail-like pyocin, the F-type, was discovered ( Takeya et al, 1969 ; Govan, 1974b ; Kuroda et al, 1979 ; Kuroda and Kageyama, 1979 , 1981 ; Michel-Briand and Baysse, 2002 ; Saha et al, 2023 ).…”
Section: A Brief History Of Ecissmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, during this period, it was found that R-type pyocins have a more efficient killing activity than headless mutants of a related phage, supporting the hypothesis that these particles are not simply defective prophages but evolved weapons ( Shinomiya and Shiga, 1979 ). Additionally, their advantage for medical use was explored, employing pyocins for P. aeruginosa typing ( Farmer and Herman, 1969 ; Rose et al, 1971 ; Edmonds et al, 1972 ; Lovrekovich et al, 1972 ; Jones et al, 1974 ; Duncan and Booth, 1975 ; Bruun et al, 1976 ; Fyfe et al, 1984 ; Schable et al, 1986 ) as well as a potential treatment against P. aeruginosa infections ( Merrikin and Terry, 1972 ; Haas et al, 1974 ). In addition to all these findings, a new type of phage tail-like pyocin, the F-type, was discovered ( Takeya et al, 1969 ; Govan, 1974b ; Kuroda et al, 1979 ; Kuroda and Kageyama, 1979 , 1981 ; Michel-Briand and Baysse, 2002 ; Saha et al, 2023 ).…”
Section: A Brief History Of Ecissmentioning
confidence: 99%
“…The usage of eCISs for potential biotechnological applications is not a recent concept. These particles were already used in the 1970s as a tool for P. aeruginosa typing or “fingerprinting” to better identify, investigate and control outbreaks ( Farmer and Herman, 1969 ; Rose et al, 1971 ; Edmonds et al, 1972 ; Lovrekovich et al, 1972 ; Jones et al, 1974 ; Duncan and Booth, 1975 ; Bruun et al, 1976 ; Fyfe et al, 1984 ; Schable et al, 1986 ). Furthermore, as multi-drug resistant bacterial infections are becoming more frequent and more difficult to treat, the high specificity of eCISs, specifically R-tailocins, has interesting potential for medical applications in the treatment of nosocomial P. aeruginosa infections.…”
Section: Biotechnological Applications Of Ecissmentioning
confidence: 99%